Heparin-induced Thrombocytopenia: IgG Binding to PF4-Heparin Complexes in the Fluid Phase and Cross-reactivity with Low Molecular Weight Heparin and Heparinoid - Newman, Peter M.; Swanson, Rebecca L.; Chong, Beng H. (Thrombosis and Haemostasis, 1998)
Early diagnosis of heparin-induced thrombocytopenia (HIT) is essential to reduce morbidity and mortality. We report an enzyme immunoassay which detects the binding of HIT IgG to PF4-heparin in the fluid phase. Our fluid phase assay produces consistently low background and can detect low levels of anti-PF4-heparin. It is suited to testing alternative anticoagulants because, unlike in an ELISA, a clearly defined amount of antigen is available for antibody binding. We were able to detect anti-PF4-heparin IgG in 26/28 (93%) HIT patients. We investigated cross-reactivity of anti-PF4-heparin antibodies with PF4 complexed to alternative heparin-like anticoagulants. Low molecular weight heparins cross-reacted with 23/26 (88%) of the sera from HIT patients while half of the HIT sera weakly cross-reacted with PF4-danaparoid (Orgaran). The thrombocytopenia and thrombosis of most of these patients resolved during danaparoid therapy, indicating that detection of low affinity antibodies to PF4-danaparoid by immunoassay may not be an absolute contraindication for danaparoid administration.